Ten-Minute Terrors: Camp Fear & Other Hideous Horrors - Fowler, Anne Bancroft (RGA Publishing Inc, 1995)
The biggest test of courage at Angela's survival camp is Fright Night. Maybe that's why the camp is nicknamed Camp Fear.
Keywords: Horror & Ghost Stories; Juvenile Fiction